The museum's identity crisis: Essay on the "being or not being" of museums. - Cerqueira, Nilo (Edições Universitárias Lusófonas, 2014)
It is important to museology, museums and especially for visitors to define concepts about the social role of the museum and the museum as an organization. For museums is important from the point of view of its delineations of activity and modes of dialogue. To Museology has value because it gives the mission often propose new guidelines to improve and moments between the museum and society. And finally, for the visitor, it is the reason, the nature of the museum settles. At the headquarters of understanding that this not called. A simple walk in the guideline of the history of advent museum, and you can notice the dissonance between theory, the θεωρία Greek, is the purely rational descriptive knowledge. Practical activity; action exercise use. In the course of these lines, we note, in the spectrum of branding, the various inconsistencies between theory and practice, the first image and the target image, between the rational and emotional, between being what want to be. Or as the article suggests, between the being or not being of museums. Keywords: Museum, Museology, Branding, Sociomuseology, Image, Positioning.